Etude de quelques propriétés biologiques des huiles essentielles de Rosmarinus officinalis de la région de Mostaganem - YAHIA BEY, SOUHILA; HAMIDI, SARA (My University, 2024)
The objective of our work is to evaluate the antimicrobial activity of essential oils obtained from a medicinal plant (Rosmarinus officinalis), vis-à-vis five pathogenic strains tested Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 33862, Candida albicans ATCC 10231, Bacillus cereus ATCC 6633, Pseudomonas aeruginosa ATCC 27853, using the disc diffusion method (Aromatogram) on a agar medium (Muller Hinton). Our work also aims to evaluate the antioxidant activity of Rosmarinus officinalis HEs using the free radical DPPH. The results of antimicrobial activity are expressed by the diameters of the inhibition zones, concerning essential oils, the results differ from one strain to another, and they are between 10,65mm and 16.56mm respectively for Pseudomonas aeruginosa ATCC 27853 and Escherichia coli ATCC 25922. In order to evaluate the antioxidant activity, it demonstrated that the IC50 values being of the order of 91.93 mg/ml for the essential oils of Rosmarinus officinalis plants and 63.06371 mg/ml for ascorbic acid. According to the results obtained, the essential oils obtained have significant antioxidant power. All the results indicate that the essential oils of Rosmarinus officinalis have a very interesting and important effect compared to the pathogenic strains tested.
Keywords: Rosmarinus officinalis; Essential oils; Pathogenic strains; antimicrobial activity; antioxidant activity